Genomic distribution of beta papillomaviruses in single eyebrow hair samples and pools of eyebrow hair samples - Fujs Komloš, Kristina (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2011)
Human beta papillomaviruses (beta-HPVs) are frequently detected in hairs and the majority of people are infected with multiple beta-HPV genotypes. This study was conducted to investigate for the first time the distribution of beta-HPV genotypes in single hair specimens and to estimate the contribution of a single hair to the beta-HPV profile obtained from a specimen made of multiple hairs pooled together. A total of 85 eyebrow hair specimens, representing 64 single hairs and 21 pools of hairs, obtained from 21 immunocompetent individuals, were tested using a reverse-line blot-based beta-HPV genotyping assay that allows identification of 25 different beta-HPVs. Overall, beta-HPV DNA was detected in 82/84 (97.6%) samples. The great majority of hair pools (19/21; 90.5%) contained multiple beta-HPVs, the mean number of identified beta-HPV genotypes per hair pool was 5.2 (ranging from 1 to 12). In individual hairs, the great majority of individual hairs (43/63; 68.3%) contained multiple beta-HPVs, the mean number of identified beta-HPV genotypes was 4 (ranging from 1 to 12). Overall, HPV-23 was the most prevalent genotype, followed by HPV-24 and HPV-38. A comparison of beta-HPV genotype distribution in pooled hair specimens and in at least one individual hair within a single patient revealed that 5/20 patients had a complete match between the number and profile of identified genotypes, 2/20 patients had the same/similar number of HPV genotypes but different genotype profile, 9/20 patients had more HPV genotypes identified in pools than in the majority of individual hairs and 4/20 patients had at least one individual hair with more HPV genotypes identified than in the corresponding pool. Our results suggest that beta-HPVs are unevenly distributed over the eyebrows and even pools made of several hairs do not necessarily provide information on the whole spectrum of HPV genotypes present in eyebrows.
Keywords: Classification; Eyebrows; Genetics; Genotip; genotipizacija; Genotype; Hair Follicle; Lasni mešiček; Obrvi; Papilloma; Papillomavirus, Human; Papilom; papiloma virusi; Papilomavirus človeški; Polimerazna, verižna reakcija; Polymerase Chain Reaction